2013 4th International Conference on Intelligent Systems, Modelling and Simulation 2013
DOI: 10.1109/isms.2013.76
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Cost Mobile Urban Environmental Monitoring System

Abstract: The increasing pace of economic development and urbanization around the world has led to serious problems of environmental pollution, particularly from automobile emissions which contributes to Global Warming. In this paper, a low-cost mobile urban environmental monitoring system is proposed using off-the-shelf open source hardware and software. The system can be installed or used in public transport vehicles, particularly in school and college buses in countries like India. A pollution map of local and region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…As proof of concept, temperature and humidity sensors have been used for monitoring environmental conditions. The data have been tagged with temporal (date and time) and spatial (latitude and longitude coordinates from on-board GPS) coordinates, and can be used to build environmental maps and environmental geographic information systems [13]. Extension of the system to coordinated mobile robot path planning, navigation with real-time obstacle avoidance using on-board vision system, and incorporation of additional sensors for environmental monitoring are straightforward, and are topics for future work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As proof of concept, temperature and humidity sensors have been used for monitoring environmental conditions. The data have been tagged with temporal (date and time) and spatial (latitude and longitude coordinates from on-board GPS) coordinates, and can be used to build environmental maps and environmental geographic information systems [13]. Extension of the system to coordinated mobile robot path planning, navigation with real-time obstacle avoidance using on-board vision system, and incorporation of additional sensors for environmental monitoring are straightforward, and are topics for future work.…”
Section: Resultsmentioning
confidence: 99%
“…A variation of this technology is the robot sensor network (e.g., [12]) which is a mobile version of wireless sensor networks with fixed nodes. An innovative, low-cost version of a mobile sensor network for outdoor air quality monitoring in India has recently been implemented using means of public transport [13]. Research has been also done on so-called robot mules that can autonomously collect environmental information [14].…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [ 32 ] present a low-cost solution based on the Arduino platform. Each Arduino is equipped with various sensors, such as CO, CO 2 , hydrogen, methane and sound.…”
Section: Related Workmentioning
confidence: 99%
“…In an attempt to overcome these disadvantages, technological based surveillance has become an alternative. Many researchers [15,[19][20][21][22] have shown that the use of mobile devices has significantly improved reporting and communication of site inspections while other researchers [23][24][25][26][27] have implemented technological based surveillance by using wireless sensors and the Web as an alternative to traditional environmental quality monitoring.…”
Section: Research Motivationmentioning
confidence: 99%